Azimuthal decorrelations and multiple parton interactions in gamma+2 jet and gamma+3 jet events in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Varelas, N.; et al. (Amer Physical Soc, 2011)
Samples of inclusive gamma + 2 jet and gamma + 3 jet events collected by the D0 experiment with an integrated luminosity of about 1 fb(-1) in p (p) over bar collisions at root s = 1.96 TeV are used to measure cross sections as a function of the angle in the plane transverse to the beam direction between the transverse momentum (p(T)) of the gamma + leading jet system (jets are ordered in p(T)) and p(T) of the other jet for gamma + 2 jet, or p(T) sum of the two other jets for gamma + 3 jet events. The results are compared to different models of multiple parton interactions (MPI) in the PYTHIA and SHERPA Monte Carlo (MC) generators. The data indicate a contribution from events with double parton (DP) interactions and are well-described by predictions provided by the PYTHIA MPI models with p(T)-ordered showers and by SHERPA with the default MPI model. The gamma + 2 jet data are also used to determine the fraction of events with DP interactions as a function of the azimuthal angle and as a function of the second jet p(T).